Myanmar’s Role in India’s Act East Policy in the Face of Challenges from China - Kiệt Lê Hoàng (MultiTech Publisher, 2023)
India and Myanmar have had a friendly, traditional neighborly relationship for many centuries. Both countries are important pillars in each other’s regional and global policies and strategies. In particular, Myanmar plays an extremely vital role in India’s Look East Policy (LEP), which evolved into the Act East Policy (AEP) since Prime Minister Narendra Modi announced it in 2014. The research results will reflect Myanmar’s position and role in India’s AEP. Therefore, the article concludes that Myanmar is currently India’s top strategic partner in Southeast Asia and the Indian Ocean.